Roll With It : Brass Bands in the Streets of New Orleans - Sakakeeny, Matt, 1971- (Book collections on Project MUSE., 2013)
Roll with it is a firsthand account of the precarious lives of musicians in the Rebirth, Soul Rebels, and Hot 8 brass bands of New Orleans.